Exosome-cargoed microRNAs: Potential therapeutic molecules for diabetic wound healing. Issue 10 (October 2022) - Lou, Ruohan; Chen, Jiali; Zhou, Fei; Wang, Chunming; Leung, Chung-Hang; Lin, Ligen
Graphical abstract: Highlights: Exosomal microRNAs are pivotal regulators of angiogenesis during wound healing. Exosomal microRNAs regulate VEGF expression and downstream signaling transduction. microRNAs cargoed by exosomes provide a prospective therapy for diabetic foot ulcers. Abstract : Diabetic foot ulcers are one of the most common complications of diabetes, requiring repeated surgical intervention and leading to amputation. Owing to the lack of effective drugs, novel therapeutics need to be explored. Decreased angiogenic factors, endothelial cell dysfunction and vascular lumen stenosis impair angiogenesis in diabetic wounds. Exosome-cargoed microRNAs are emerging as pivotal regulators of angiogenesis during wound closure. Herein, we summarize the up-to-date knowledge of exosomal microRNAs in modulating angiogenesis and accelerating diabetic wound healing, as well as their targets and underlying mechanisms. Exosomal microRNAs could be therapeutics with negligible rejection complications and good compatibility to treat diabetic foot ulcers.